(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2021)
The rapid technological development of our time began to show its dark face, and that by using it to develop tools for killing and destroying, So we can say that man has the ability to destroy himself and end his existence with his hand. The weapons of mass destruction of all nuclear, chemical and biological types are developed initially in order to create some kind of balance of power between states ,but the danger is no longer limited to the use of these weapons by a state against another state, Especially, that all countries have international obligations to preserve peace and security, The real danger lies in the terrorists putting their hands on these weapons and using them without deterrence or control. No longer get huge funding or having a competent scientific expertise is an obstacle to the use of these weapons by terrorists, Especially, after their attempts to obtain or develop and use it. Therefore, the world should be aware of schemes of terrorist groups with regard to the use of these weapons, and the extent of their access or development for them, In addition to, monitoring the technology and the modern technologies that would remove obstacles that may encounter terrorist groups and prevent the use of these weapons with their full effectiveness.